2019
DOI: 10.1111/sji.12749
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory role of chitosan‐based nanoparticles and oligosaccharides in cyclophosphamide‐treated mice

Abstract: Chitosan, the deacetylated form of chitin, a natural polysaccharide, is known for its various biomedical applications. The present study aimed at exploring the immunomodulatory properties of chitosan (CSNP) and gallic acid‐grafted chitosan (cGANP) nanoparticles in mice model of cyclophosphamide (CPA)‐induced immunosuppression. In addition, chitooligosaccharides, the hydrolysed form of chitin and chitosan, were also evaluated for its potential against immunosuppression in mice. CPA (80 mg/kg/ip) induced signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…It has been confirmed that COS administration by intraperitoneal injection and intragastric administration significantly improved the phagocytic function of mouse peritoneal macrophages, increased the index of immune organs such as thymus and spleen, stimulated lymphocytes to secrete IL-2 cytokines, and enhanced the activity of NK cells [21,22]. COS stimulated the secretion of other cytokines by activating macrophages, to then produce a cascade reaction [23].…”
Section: Introductionmentioning
confidence: 83%
“…It has been confirmed that COS administration by intraperitoneal injection and intragastric administration significantly improved the phagocytic function of mouse peritoneal macrophages, increased the index of immune organs such as thymus and spleen, stimulated lymphocytes to secrete IL-2 cytokines, and enhanced the activity of NK cells [21,22]. COS stimulated the secretion of other cytokines by activating macrophages, to then produce a cascade reaction [23].…”
Section: Introductionmentioning
confidence: 83%
“…It has been reported that chitosan-based nanosystems could significantly increase the secretion of IFN-γ by Th1 cells and stimulate the cell-mediated immunity. Compared to chitosan oligosaccharides, the chitosan nanoparticles showed an enhanced immunomodulatory effect (1.2–1.5-fold), indicating the immunomodulatory effect could be tuned by aggregation of nanoparticles [ 211 ]. Wardani et al [ 212 ] also applied chitosan nanoparticles to animal models and concluded that these nanoparticles could effectively stimulate immune responses and have a therapeutic potential for immunotherapy.…”
Section: Chitosan-based Nanomedicinesmentioning
confidence: 99%
“…A very recent study, done on chitosan-based NPs and oligosaccharides in cyclosporin treated mice, found the NPs to be superior to chitosan itself in terms of their immunomodulatory abilities, which was attributed to the unique characteristics and biological activities of the NPs. The authors argue that physiochemical properties of NPs, per se, influence their interaction with immune cells to induce both desirable effects and unavoidable, undesirable nanotoxicity [96].…”
Section: Leukocyte Function In Hemostasis and The Mechanisms Involmentioning
confidence: 99%